Pengaruh Pergaulan Teman Sebaya terhadap Kecerdasan Interpersonal Mahasiswa Di Sekolah Tinggi Katolik Santo Yakobus Merauke - Yohanes Hendro Pranyoto; Videlis Nilo Leba (JURNAL PASTORAL KATEKETIK, 2024)
This topic is inspired by the situations and conditions that occur on the campus of the Catholic College of Saint Yakobus Merauke that quite a lot of students who are more dominant have associations that have an impact on interpersonal intelligence so that this thesis aims to see how much influence peer association has on the interpersonal intelligence of students at the Catholic College of Saint Yakobus Merauke. This type of research is quantitative with a regression analysis model. The sample in this study were students of the Catholic College of Saint Yakobus Merauke from semester II-XII as many as 132 people. The instrument used is a questionnaire with a semantic scale model developed in 98 statements with two variables, namely peer association (50) and interpersonal intelligence (48). From the validity test results at a significant level of 5%, N = 132 people with a critical value of 0.1 and the results of the peer association reliability test obtained an alpha coefficient of 0.903 means the reliability of the instrument is moderate and the reliability of inerpersonal intelligence obtained an alpha coefficient of 0.908 means the reliability of the instrument is very high. From the results of the simple linear regression test with a significant level of 5%, an r² value of 0.473 (47.3%) was obtained, which means that there is an influence even though the effect is weak, meaning that peer association does not have a significant impact on student interpersonal intelligence. Other variables that affect student interpersonal intelligence are 52.7%, which shows that Ha is accepted and Ho is rejected. This means that peers have an effect on student interpersonal intelligence. Based on the results of this study, it is recommended that students need to increase socialization both within the scope of campus and outside campus and there is support from lecturers. In an effort to improve socialization in the world of education, namely creating a healthier, more inclusive and supportive learning environment. Increased interaction between peers has the potential to create a social environment that is harmonious and conducive to the personal development of students.